Jobless Now, Sick Later? Investigating the Long-term Consequences of Involuntary Job Loss on Health - Mathis Schröder (Advances in Life Course Research, 2013)
In the light of the current economic crises which in many countries lead to business closures and mass lay-offs, the consequences of job loss are important on various dimensions. They have to be investigated not only in consideration of a few years, but with a long-term perspective as well, because early life course events may prove important for later life outcomes. This paper uses data from SHARELIFE to shed light on the long-term consequences of involuntary job loss on health. The paper distinguishes between two different reasons for involuntary job loss: plant closures, which in the literature are considered to be exogenous to the individual, and lay-offs, where the causal direction of health and unemployment is ambiguous. These groups are separately compared to those who never experienced a job loss. The paper uses eleven different measures of health to assess long-term health consequences of job loss, which has to have occurred at least 25 years before the current interview. As panel data cannot be employed, a large body of variables, including childhood health and socio-economic conditions, is used to control for the initial conditions. The findings suggest that individuals with an exogenous job loss suffer in the long run: men are significantly more likely to be depressed and they have more trouble knowing the current date. Women report poorer general health and more chronic conditions and are also affected in their physical health: they are more likely to be obese or overweight, and to have any limitations in their (instrumental) activities of daily living. In the comparison group of laid-off individuals, controlling for the initial conditions reduces the effects of job loss on health – proving that controlling for childhood conditions is important.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in “Advances in Life Course Research”. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Advances in Life Course Research 18 (2013), 1, pp. 5-15 and is online available at http://dx.doi.org/10.1016/j.alcr.2012.08.001
Keywords: 330; Unemployment; Health; Long-term consequences; Plant closures; Kündigung; Gesundheit; Arbeitslosigkeit; Auswirkungen